1988
DOI: 10.1073/pnas.85.16.6167
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of bipotential glial precursors into oligodendrocytes is promoted by interaction with type-1 astrocytes in cerebellar cultures.

Abstract: The differentiation of bipotential precursors of oligodendrocytes (OL) and type-2 astrocytes (AS) was followed in primary cultures from 8-day postnatal rat cerebellum by labeling the cells with the antibodies LB1 (which binds to the surface disialoganglioside GD3 present in glial precur- "neuron-like" fashion (6,11), are sensitive to kainic acid (V. Gallo, R. Suergiu, C. Giovannini, and G.L., unpublished data), and express chondroitin sulfate (7). The bipotential cerebellar glial precursors pass through four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…These experiments demonstrated that the addition of a single dose of ACM, together with daily additions of 10 ng/ml of bFGF, was associated with a greater extent of oligodendrocytic differentiation after 3 days that was seen with the addition of just 0.03 ng/ml daily of bFGF alone to similar cultures of cells. It therefore seems likely to us that one aspect of the effect of astrocytes is to actively promote the differentiation of 0-2A progenitors into oligodendrocytes, as has also been suggested by other authors (Aloisi et al, 1988;Dutly and Schwab, 1991). Although it has been suggested (Dutly and Schwab, 1991) that such an effect might be mediated by insulin-like growth factor I (IGF-I), recent studies (Barres et al, 1992) have suggested that the effects on 0-2A progenitor differentiation attributed to this protein (McMorris et al, 1986) may have been due to the ability of IGF-I to promote the survival of oligodendrocytes.…”
Section: Discussionmentioning
confidence: 70%
“…These experiments demonstrated that the addition of a single dose of ACM, together with daily additions of 10 ng/ml of bFGF, was associated with a greater extent of oligodendrocytic differentiation after 3 days that was seen with the addition of just 0.03 ng/ml daily of bFGF alone to similar cultures of cells. It therefore seems likely to us that one aspect of the effect of astrocytes is to actively promote the differentiation of 0-2A progenitors into oligodendrocytes, as has also been suggested by other authors (Aloisi et al, 1988;Dutly and Schwab, 1991). Although it has been suggested (Dutly and Schwab, 1991) that such an effect might be mediated by insulin-like growth factor I (IGF-I), recent studies (Barres et al, 1992) have suggested that the effects on 0-2A progenitor differentiation attributed to this protein (McMorris et al, 1986) may have been due to the ability of IGF-I to promote the survival of oligodendrocytes.…”
Section: Discussionmentioning
confidence: 70%
“…In particular, bipotential progenitors already expressing the early oligodendroglial marker 0 4 could be largely induced to differentiate into astrocytes under the influence of GFAP-inducing serum factors (Aloisi et al, 1988;Levi et al, 1987;Trotter and Schachner, 1989). The limited number and the transient detectability of 04+/GFAP+ cells in our cultures did not allow us to establish whether these cells would eventually give rise to astrocytes or to oligodendrocytes.…”
Section: Significance Of Cells With a Mixed Astroglialmentioning
confidence: 74%
“…One report (23) does describe the use of a retroviral vector carrying a temperature-sensitive mutant of the SV40 large-T-antigen gene to establish a cell line (SF11) from mouse brain that stably expresses GFAP. However, isolation of the GFAP-expressing line was a rare event (1 out of 19), and the line itself was not examined for other characteristics of type 1 astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These are differentiated cells defined by specific morphological and phenotypic marker criteria (17). Cultures of type 1 astrocytes can be partially purified from other cell types by mechanical and/or immunological techniques (18,19). However, such cultures are still clearly heterogeneous (9,(13)(14)(15) and may not be the most useful model for investigations of functionally specialized astrocyte subsets.…”
Section: Introductionmentioning
confidence: 99%